Følelsernes opdragelse - Buchmann, Sabeth; Ellebjerg Hansen, Cecilie; Schultz, Laura Luise Schultz (Peripeti, 2012)
The essay discusses the role of affect and emotions in Yvonne Rainer's autobiography 'feelings are facts. a life' from 2006 in relation to her films and choreographic work. Buchmann traces the emotional impact on Rainer's formalist work and argues that the autobiography may be seen as a supplementary work to Rainer's artistic work. Implicitly, Buchmann raises the question of how emotional strength may be used as an artistic force.